High-resolution seismic imaging of gas accumulations and seepage in the sediments of the Ria de Aveiro barrier lagoon (Portugal) - Duarte, H.
Methane is a powerful greenhouse gas and an important energy source. The global significance and impact in coastal zones of methane gas accumulation and seepage in sediments from coastal lagoon environments are still largely unknown. This paper presents results from four high-resolution seismic surveys carried out in the Ria de Aveiro barrier lagoon (Portugal) in 1999, 2002 and 2003. These comprise three chirp surveys (RIAV99, RIAV02, RIAV02A) and one boomer survey (RIAV03). Evidence of extensive gas accumulation and seepage in tidal channel sediments from the Ria de Aveiro barrier lagoon is presented here for the first time. This evidence includes: acoustic turbidity, enhanced reflections, acoustic blanking, domes, and acoustic plumes in the water column (flares). The stratigraphy and structural framework control the distribution and extent of gas accumulations and seepage in the study area. In these shallow systems, however, tidal altitude variations have a significant impact on gas detection using acoustic methods, by changing the raw amplitude of the enhanced seismic reflections, acoustic turbidity, and acoustic blanking in gas-prone areas. Direct evidence of gas escape from drill holes in the surrounding area has shown that the gas present in the Ria de Aveiro consists of biogenic methane. Most of the gas in the study area was probably generated mainly in Holocene lagoon sediments. Evidence of faults affecting the Mesozoic limestones and clays underlying some of the shallow gas occurrences, and the presence of high-amplitude reflections in these deeper units raise the possibility that some of this gas could have been generated in deeper sedimentary layers, and then migrated upward through the fractured Mesozoic strata.